2009
DOI: 10.1007/978-3-642-01799-5_20
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Flock-Based Collaborative Clustering Algorithms

Abstract: Abstract.Inspiration from nature has driven many creative solutions to challenging real life problems. Many optimization methods, in particular clustering algorithms, have been inspired by such natural phenomena as neural systems and networks, natural evolution, the immune system, and lately swarms and colonies. In this paper, we make a brief survey of swarm intelligence clustering algorithms and focus on the flocks of agents-based clustering and data visualization algorithm, (FClust). A few limitations of FCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 25 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…In both algorithms, the ideal distance was computed using (28). Our experiments showed that since Web usage data followed a power low distribution [129], (24) resulted in a grossly over-estimated similarity threshold and led to no cluster formation, as mentioned in Section 2.5.2.…”
Section: Fclust-annealing Results For 2d and Web Usage Datasetsmentioning
confidence: 74%
See 4 more Smart Citations
“…In both algorithms, the ideal distance was computed using (28). Our experiments showed that since Web usage data followed a power low distribution [129], (24) resulted in a grossly over-estimated similarity threshold and led to no cluster formation, as mentioned in Section 2.5.2.…”
Section: Fclust-annealing Results For 2d and Web Usage Datasetsmentioning
confidence: 74%
“…Our hybrid approach reduces the quadratic complexity of FClust to linear complexity, and performs similarly to FClust, but has the advantage of fewer iterations for clustering large, high-dimensional data such as web usage data. Hybrid algorithms were tested on several datasets including UCI machine learning data sets and Web server logs and our experiments confirmed their superiority, both in terms of quality of the final results and computational costs [128,129].…”
Section: Contributions Of This Dissertationmentioning
confidence: 65%
See 3 more Smart Citations